The effects of carisoprodol on endochondral ossification: A review of the literature and implications for bone health - YRKM Sai (Annals of Musculoskeletal Medicine - Peertechz Publications, 2022)
Carisoprodol is a medication commonly prescribed for musculoskeletal pain, but recent studies have raised concerns about its potential negative effects on bone development and health, particularly in relation to endochondral ossification. Endochondral ossification is a critical process that involves the transformation of cartilage into bone, which is essential for the formation of long bones in the body. Carisoprodol has been shown to reduce the activity of osteoblasts while increasing the activity of osteoclasts, leading to an imbalance in bone formation and resorption. Studies also suggest that carisoprodol may inhibit osteoblast differentiation, decrease bone density, strength, and microarchitecture, and affect the expression of genes involved in endochondral ossification. These negative effects may be due, in part, to its inhibition of the Wnt signaling pathway. Healthcare providers should carefully consider the potential risks of carisoprodol on bone development and health when prescribing this medication. Alternative treatments may be considered for patients at high risk of bone-related complications.